3, 4-Seco-spirostane sapogenins with cytotoxic activity from Allium umbilicatum boiss. (June 2015) - Zolfaghari, Behzad; Sadeghi, Masoud; Troiano, Raffaele; Lanzotti, Virginia
Graphical abstract: Highlights: Two new seco-spirostane sapogenins were isolated from Allium umbilicatum Boiss . Compounds were based on the rare 3, 4-seco-spirostane skeleton. This is the first report of such skeleton from natural sources. Cytotoxicity activity of seco-umbilicagenins A and B was evaluated. Abstract: Two new sapogenins, named seco-umbilicagenins A and B (1 and 2), possessing a new chemical structure based on a 3, 4-seco-spirostane skeleton, were isolated from Allium umbilicatum Boiss . The chemical structures of seco-umbilicagenins A and B were established through a combination of extensive spectroscopic analysis, mainly nuclear magnetic resonance spectroscopy and mass spectrometry, and chemical methods as (2 S, 25 R )-2, 5α, 6β-trihydroxy-3, 4-seco-spirosta-3, 4-dioic acid (1 ) and (2 S, 25 R )-2, 4, 5α-trihydroxy-6- oxo -3, 4-seco-spirostan-3-oic acid (2 ). Interestingly, the isolated compounds exhibited cytotoxic activity on J-774, murine monocyte/macrophage, and WEHI-164, murine fibrosarcoma, cell lines. To the best of our knowledge this is the first time that 3, 4-seco-spirostane sapogenins are isolated from natural sources, being this skeleton obtained by synthetic modification of intact sapogenins.